(untitled) (Conferencea, 2022)
The article analyzes technological machines, their types, operation, and methods, as well as their shortcomings and the scientific and research work carried out on their elimination, used in the process of fibre cleaning, which is the main product of spinning enterprises. The authors proposed new technological methods to overcome the shortcomings identified as a result of the analysis